Building condition assessment at Kuarters JKR Kuala Krai, Kelantan / Amirul Hilmi Saidi - Saidi, Amirul Hilmi (2017)
Building Condition Assessment is often referred as a pre-construction condition survey and this survey is to carry out survey the level of condition of the adjoining properties, prior to the commencement of construction activities. The Building Condition Assessment is to inspect the building or other structure, at a certain date, to capture defects that already existing in a site which that site will do the survey work before piling and construction work will start. It is often carried out on regular basis for certain types of property. Usually it is presented in the form of a schedule of condition.